Anthropogenic Impacts Facilitate Native Fish Hybridization in the Bonneville Basin of Western North America. Issue 1 (2nd January 2017) - Bangs, Max R.; Douglas, Marlis R.; Thompson, Paul; Douglas, Michael E.
Abstract: Habitat modification and introduced species are impacting native fishes in western North America, a situation now exacerbated by drought and anthropogenic water acquisition. One species of concern, the Bluehead Sucker Catostomus discobolus in the Bonneville basin of Utah, Idaho, and Wyoming, has experienced sharp population declines potentially augmented by hybridization with native Utah Sucker C. ardens . To evaluate this situation, we sequenced three diagnostic nuclear DNA loci and two mitochondrial genes across 81 Bluehead Suckers, 74 of which were collected in a basinwide genetic assessment and 7 from a targeted morphological evaluation. Combined, we detected 14 hybrids from the single site in the Bear River and the three sites in the Weber River that hosts the three largest remaining populations in the basin. All individuals sampled as putative hybrids were confirmed as F1 hybrids, ascertaining efficacy of field-based morphological identifications. Hybridization may be especially problematic for the numerically reduced Bluehead Sucker because it can further depress recruitment. However, no evidence of post-F1 backcrosses was found, suggesting in turn that hybrids are not reproducing, although the reasons for this are currently not understood. These results underscore the need to quantify the proportion of Bluehead Sucker recruitment lost to hybridization. Received January 6, 2016; accepted August 31, 2016